Law Enforcement Towards Illegal Logging Perpetrators Based on Law Number 18 of 2013 Concerning Prevention and Eradication of Illegal Logging (P3H) - Muhammad Irvan Fachrozi (IHSA Institute, 2022)
Illegal logging or illegal logging is logging, transporting or selling timber that is illegal or does not have a permit from local authorities. Deforestation, especially in the form of illegal logging, has caused state losses, damaged socio-cultural life and the environment, and increased global warming. Forest destruction has become a crime that has extraordinary, organized and transnational impacts carried out with a sophisticated modus operandi, has threatened the survival of people's lives so that in the context of preventing and eradicating effective forest destruction and providing a deterrent effect, a strong and capable legal basis is needed. ensure the effectiveness of law enforcement. The purpose of the article with the title